Exploring the Processes of Informal Justice System in Resolving Gender-Based Violence: A Case Study of Mansehra City - Sheeraz Farooq; Taimoor Shehzad (Social Science Review Archives, 2025)
Gender-based Violence (GBV) remains a prevalent issue in Pakistan. The GBV cases are often settled through Informal Justice System which functions more as a reconciliatory body than a provider of justice to victims. This study explores the processes of the informal justice system, specifically the Jirga, in addressing GBV within the context of Mansehra City. The research examines the structure, function, and effectiveness of the Jirga in resolving GBV cases, focusing on the challenges faced by women seeking justice through this system. Issues such as patriarchal practices, lack of female representation, and societal pressures often undermine the resolution process, leaving female victims with limited options for justice. Through qualitative methods, including interviews with female respondents and other key actors, the study reveals that while the Jirga provides a quicker, more accessible, and culturally relevant means of dispute resolution, it frequently perpetuates gender biases and patriarchal norms. Main findings indicate that women in joint family structures experience higher incidences of GBV due to domestic power struggles, while nuclear families report fewer conflicts but face financial constraints. The preference for the Jirga, cited by 90% of respondents, stems from its cost-effectiveness and cultural alignment, yet its male-dominated structure often marginalizes women's voices and concerns. The study highlights the need for reforms in formal and informal justice systems, emphasizing the importance of incorporating gender sensitivity and inclusivity. Recommendations include fostering community awareness, enhancing women's education, and creating hybrid justice mechanisms that integrate the accessibility of the informal system with the procedural rigor of the formal system. The findings underscore the critical role of education and societal support in reducing GBV and fostering a safer environment for women in Mansehra City.